Eksistensi Subak Di Tengah Gempuran Alih Fungsi Lahan - Ni Kade Seri Andayani (Pramana: Jurnal Hasil Penelitian, 2021)
Subak as an irrigation system for the life manager of the farmers. System formed from hundreds of years ago was the implementation of the community mutual cooperation system in carrying out life as a farmer. The process that occurred in it from the spiritual aspect there was a temple of Ulun Suwi as a place of worship, there was a stages of each land processing process to planting the agreed rice. The onslaught of the land function makes the region of the Subak power reduced or even the remaining only the subdiability of the subject, so that more depth assessment will be needed the essence of the subak so that it must be maintained, through qualitative education and various data sources presented in the form of qualitative descriptions. The results of the study explained the existence of the Subak irrigation system was affected by how the land area managed by the Subak. When it occurs over the function of land that was originally a paddy field becoming a housing building would certainly affect the territory of the power of Subak. The initial function of Subak in accordance with the above explanation is that the irrigation system changes only as Swagina temple because it no longer has rice fields. Subak Temple is a subak ulun as the implementation of the concept of Prahyangan is no longer stomached by Sekaa Subak because the subject has turned into a building, as well as the subak irrigation system that does not run because there are no agricultural activities in the area.